(untitled) (Research, Society and Development, 2022)
Introduction: Academic experience brings challenges that can, in certain contexts, lead to the emergence of anxiety disorders. Objectives: To verify the prevalence of anxiety disorders in undergraduates of health courses at a Public University in the State of Pará; verify the relationship between anxiety disorder, social support received, socioeconomic and demographic factors. Methodology: The research was quantitative analytical observational transversal, carried out with undergraduates from the following health sciences courses: Occupational therapy, physical education, biomedicine, medicine and physiotherapy, through field research, with application of an online questionnaire, in February to July 2021, using the Hamilton Anxiety Assessment Scale as the primary variable, and the Social Support Satisfaction Scale and the socioeconomic cultural variable as secondary variables, through a questionnaire. Results: With regard to the higher prevalence of anxiety disorders, it was detected that it was higher in Occupational Therapy and Physical Education courses, higher among students attending the 3rd and 2nd years, higher in females, moreover, it showed that the lower average individual income of students, and those who had less social support received, the higher were the scores for anxiety disorders. Conclusion: The research revealed associations between the prevalence of anxiety disorders in healthcare courses and the factors that contribute to this situation. It is essential that students and faculty seek the best guidance from the academic in order to prevent the problems associated with this pathology.